Analysis of Hydrodynamic Parameters Effect on the Hydropurification Reactor Operation through Numerical Simulation - Azarpour, A. (Elsevier Ltd, 2017)
In the class of three-phase catalytic reactors, trickle-bed reactors (TBRs) are the most extensively used in industry. They are utilized in petrochemicals, petroleum, chemicals, waste treatment, electrochemical and biochemical processing, and many other applications. One of the most significant applications of TBRs is their utilization in the process of purification. Since the purified product has to meet the required specifications of a high quality chemical, the TBRs operation control is very critical. Considerable fluctuation of the operating parameters values adversely affects the reactor efficient performance. In this paper, the effect of hydrodynamic parameters on the hydropurification TBR operation is investigated considering the product quality. A first principle heterogeneous model incorporating the hydrodynamic parameters and catalyst deactivation has been developed to analyze the reactor performance under the fluctuation of the hydrodynamic parameters. The devised model along with its mathematical solution has been coded into MATLAB R2016a environment. The results reveal that the deviation of hydrodynamic parameters of liquid holdup and gas holdup considerably influence the efficiency of the purified terephthalic acid reactor operation in term of product quality. Moreover, the impact of liquid holdup on the reactor operation is more than gas holdup in term of product quality. These research findings might be applied into an actual operating system mentioning that the deviation from trickling flow regime is to be avoided in the reactor. © 2017 The Authors. Published by Elsevier Ltd.